2009
DOI: 10.1249/mss.0b013e31818b98e6
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors to Medial Tibial Stress Syndrome

Abstract: This study established that the factors most influencing MTSS development were previous history of MTSS and stress fracture, years of running experience, and orthotic use. These data demonstrate the importance of establishing a thorough history before the start of the season so that athletes who might be at risk for MTSS development can be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(122 citation statements)
references
References 21 publications
7
112
1
2
Order By: Relevance
“…Hubbard et al, demonstrated the trend of a significant relationship between MTSS and a previous history of the condition in college athletes. The results included that 87% of the MTSS group had a previous history as opposed to only 16% of the healthy group [9]. Another study including 26 recruits with a previous history demonstrated the same relationship.…”
Section: Symptom Presentationmentioning
confidence: 82%
See 4 more Smart Citations
“…Hubbard et al, demonstrated the trend of a significant relationship between MTSS and a previous history of the condition in college athletes. The results included that 87% of the MTSS group had a previous history as opposed to only 16% of the healthy group [9]. Another study including 26 recruits with a previous history demonstrated the same relationship.…”
Section: Symptom Presentationmentioning
confidence: 82%
“…Four studies included only runners [5][6][7][8], two included military personnel [1,3], and five included athletes of different sports [2,[9][10][11][12]. The disease severity of participants within the studies varied, as some were deemed "healthy" prior to study initiation while other were already diagnosed with MTSS.…”
Section: Subject Descriptionmentioning
confidence: 99%
See 3 more Smart Citations